Regional and sex inequalities of avoidable mortality in Italy: A time trend analysis - Davide Golinelli; Giovanni Guarducci; Andrea Sanna; Jacopo Lenzi; Francesco Sanmarchi; Maria Pia Fantini; Emanuele Montomoli; Nicola Nante (Elsevier, 2023)
Objectives: This study provides a comprehensive analysis of avoidable mortality (AM), treatable mortality (TM), and preventable mortality (PM) across Italy, focusing on region- and gender-specific inequalities over a 14-year period. Study design: Time-trend analysis (2006-2019). Methods: The study was conducted using mortality data from the Italian Institute of Statistics to evaluate the extent and patterns of AM, TM, and PM in Italy. Biennial age-standardized mortality rates were calculated by gender and region using the joint OECD/Eurostat list. Results: The overall AM rates showed a large reduction from 2006/7 (221.0 per 100,000) to 2018/9 (166.4 per 100,000). Notably, females consistently displayed lower AM rates than males. Furthermore, both gender differences and the North-South gap of AM decreased during the period studied. The regions with the highest AM rates fluctuated throughout the study period. The highest percentage decrease in AM from 2006/7 to 2018/9, for both males (−41.3 %) and females (−34.2 %), was registered in the autonomous province of Trento, while the lowest reduction was observed in Molise for males (−17.4 %) and in Marche for females (−10.0 %). Conclusions: Remarkable gender and regional differences in AM between 2006 and 2019 have been recorded in Italy, although they have decreased over years. Continuous monitoring of AM and the implementation of region- and gender-specific interventions is essential to provide valuable insights for both policy and public health practice. This study contributes to the efforts to improve health equity between Italian regions.